May antidepressant drugs worsen the conditions they are supposed to treat? The clinical foundations of the oppositional model of tolerance - Giovanni A. Fava (SAGE Publishing, 2020)
In recent years there has been a considerable debate on antidepressant drugs. Continued drug treatment with antidepressant medications may stimulate processes that run counter to the initial acute effects of a drug. The oppositional model of tolerance may explain loss of treatment efficacy during maintenance treatment and the fact that some side effects tend to occur only after a certain time. These processes may also direct the illness into a treatment-unresponsive course, including manifestations of bipolar disorder or paradoxical reactions. When drug treatment ends, oppositional processes no longer encounter resistance, resulting in potential onset of new withdrawal symptoms, persistent post-withdrawal disorders, hypomania, and resistance to treatment if it is reinstituted. In all these cases, antidepressant medications may constitute a form of iatrogenic comorbidity, which increases chronicity and vulnerability to depressive episodes. Antidepressant medications are essential drugs for the treatment of major depressive episodes. They are less likely, however, to provide protection for relapse prevention. Current prescription practices need to be reformulated in light of consideration of vulnerabilities and adverse effects of treatment. The oppositional model of tolerance provides a conceptual framework for weighing all these elements in the individual case. The model does not appear to apply to all patients who undergo treatment with AD, but only to a part of them. Studying the variables that are associated with such occurrence in certain patients and not in others would be one of the most important tasks of current therapeutic research. Current diagnostic systems in psychiatry do not consider the iatrogenic components of psychopathology, and can be applied to only patients who are drug free. They are suited for a patient who no longer exists: most of the cases that are seen in psychiatric clinical practice receive psychotropic drugs and such treatment is likely to affect prognosis and treatment choices.